Challenges in Maternal and Child Health Routine Data Administration in Indonesia: A Qualitative Study - Arief Priyo Nugroho; Diyan Effendi; Zulfa Auliyati Agustina; Asep Kusnali; Siti Maimunah; Irfan Ardani; Ratna Widyasari (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Maternal and child health (MCH) routine data is essential in making a good health-relatedpolicy. However, the quality of MCH routine data in Indonesia is doubted, and thus the Indonesian governmentrelies heavily on the survey data for policymaking. This condition raises questions about where the problemsexist in routine data recording stages. This study aims to explore the barriers and strategies of MCH routinedata recording by the administrators in the primary healthcare center.Method: This study was qualitativeresearch conducted in Buru Regency, Ambon City, Purworejo Regency, and Surakarta City from May toNovember 2020. The data collections were intended to understand administrators’ efforts to deal with the datarecording problems. Data triangulation was performed through in-depth interviews with primary healthcarecenter staff and observations on daily routine data administration practices.Results: The study demonstratedchallenges in the MCH routine data administration context. The first problem is behavioral contexts lead toincorrect input and delay data submission. Second, technical determinant shows the lack of integration thatleads to repetitive data recording and data fragmentation. The third was the organizational problem suchas lack of inter and intra-departmental coordination in data sharing, infrastructure, and human resourceshortage.Conclusion: The findings elucidate the problem of administrative structures in the implementationof routine data policy. A comprehensive response to cope with routine data policy implementation contextis needed. Existing maternal and child healthcare routine data requires structural administration refinementthat provides a context for implementing reliable routine data recording of maternal and child health.